Market variables influence customer behavior toward coffee business growth - Montajula Suvattanadilok (My University, 2024)
This study investigates the impact of market engagement strategies—specifically market involvement, customer centricity, employee empowerment, and market innovation—on consumer behavior and business growth within the Thai coffee industry. Recognizing the pivotal role these factors play in shaping consumer preferences and fostering business expansion, this research aims to provide a comprehensive analysis of their influences.
Keywords: Consumer behaviour; Innovation and Socioeconomic Development